2018
DOI: 10.1016/j.celrep.2018.03.026
|View full text |Cite
|
Sign up to set email alerts
|

Shp-2 Is Dispensable for Establishing T Cell Exhaustion and for PD-1 Signaling In Vivo

Abstract: In chronic infection and cancer, T cells acquire a dysfunctional state characterized by the expression of inhibitory receptors. In vitro studies implicated the phosphatase Shp-2 downstream of these receptors, including PD-1. However, whether Shp-2 is responsible in vivo for such dysfunctional responses remains elusive. To address this, we generated T cell-specific Shp-2-deficient mice. These mice did not show differences in controlling chronic viral infections. In this context, Shp-2-deleted CD8 T lymphocytes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
98
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(102 citation statements)
references
References 44 publications
2
98
0
1
Order By: Relevance
“…Taken together, results from the SHP1/SHP2 KO experiments demonstrate that BTLA:SHP1 complex can dephosphorylate both TCR and CD28, whereas BTLA:SHP2 or PD-1:SHP2 complex only dephosphorylate CD28 (Fig 5). We note that a recent study suggested that SHP2 is dispensable for PD-1 to cause T cell exhaustion (Rota et al, 2018), indicating that PD-1 might have other effectors. However, here we find that SHP2 KO completely abolishes the ability of PD-1 to inhibit CD28 phosphorylation and IL-2 secretion, suggesting that SHP2 is the major effector for PD-1 in T cells.…”
Section: Shp1 Dephosphorylates Both Tcr and Cd28 While Shp2 Dephosphomentioning
confidence: 73%
See 1 more Smart Citation
“…Taken together, results from the SHP1/SHP2 KO experiments demonstrate that BTLA:SHP1 complex can dephosphorylate both TCR and CD28, whereas BTLA:SHP2 or PD-1:SHP2 complex only dephosphorylate CD28 (Fig 5). We note that a recent study suggested that SHP2 is dispensable for PD-1 to cause T cell exhaustion (Rota et al, 2018), indicating that PD-1 might have other effectors. However, here we find that SHP2 KO completely abolishes the ability of PD-1 to inhibit CD28 phosphorylation and IL-2 secretion, suggesting that SHP2 is the major effector for PD-1 in T cells.…”
Section: Shp1 Dephosphorylates Both Tcr and Cd28 While Shp2 Dephosphomentioning
confidence: 73%
“…PD-1 associated SHP2 was shown to dephosphorylate co-stimulatory receptors CD28 and CD226, with a much weaker effect on the phosphorylation of the immunoreceptor-tyrosine-based-activation motif (ITAM) of TCR (Hui et al, 2017;Wang et al, 2018). However, a recent study showed that SHP2 might be dispensable for PD-1 to contribute to T cell exhaustion (Rota et al, 2018), raising the question of whether SHP2 is the major effector of PD-1. It is also unclear whether and how SHP1 contributes to PD-1 function.…”
Section: Introductionmentioning
confidence: 99%
“…CD6 interacts with SHP2 phosphatase (19,46), central to PD-1 mediated suppression of T-cell responses following PD-1 ligand binding (25,47). Moreover, SHP2 modulates select T-cell exhaustion features in chronic LCMV infection (48). Here, expression of SHP2 was significantly elevated on CD6 + PD-1 + CD8 + T-cells compared to CD6 − PD-1 + CD8 + T-cells, suggesting that CD6 over-expression on CD8 + T-cells during chronic infection may lead to formation of an inhibitory signaling hub composed of CD6, PD-1 and SHP2, resulting in attenuation of T-cell responses.…”
Section: Discussionmentioning
confidence: 99%
“…Supporting to this pattern is the increased potential for phosphatase activity, in CD57 hi compared to CD57 lo TFH cells. Compared to CD57 lo , CD57 hi TFH cells express higher levels of SHP-2, an inhibitor of TCR signaling (51,52), significantly lower levels of CD150, a receptor that can affect the phosphatase activity by recruiting either SHIP or SHP-2 phosphatases (33) and marginally higher levels of PTEN. Therefore, CD57 hi TFH cells have a potentially higher capacity for tyrosine dephosphorylation compared to CD57 lo TFH cells that could contribute to the observed pTyr profiles in peripheral synaptic microclusters, the sites where TCR signal is sustained (53).…”
Section: Differentiation Of Tfh Cells Was Associated With Dramatic Chmentioning
confidence: 99%